Literasi Keuangan dan Gaya Hidup Mahasiswa dalam Manajemen Keuangan - Igga Oktavia; Cynthia Eka Violita; Nikmatul Lailiyah; Syarifah Nadia (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2026)
Financial literacy and lifestyle are two important factors influencing students' ability to manage their personal finances. Students are in a transitional phase toward financial independence and are therefore required to make rational financial decisions amidst the influence of modern lifestyles. This study aims to understand how students interpret financial literacy and lifestyle in their daily financial management practices. This study used a qualitative approach with descriptive methods. Data were collected through in-depth interviews and observations of active students from various backgrounds. The results indicate that students generally understand the basic concepts of financial literacy, such as managing pocket money and preparing a simple budget. However, the application of this financial literacy is often suboptimal due to the influence of a consumptive lifestyle and social pressures. This study provides important implications for the development of contextual financial literacy education programs in higher education environments. The implication of this research is the importance of developing financial literacy education programs that are more contextual and relevant to students' lifestyles so they can manage their personal finances more wisely and effectively.